Faith and Women in Late Medieval English Sermons - Barr, Beth Allison (Fides et historia, 2020)
An essay is presented which explores the Christian faith of women based on referenced biblical passages in Middle English sermons. Topics discussed include the obedience and faithfulness demonstrated by women to God, the concept of faith for medieval Christians which may be expressed through charitable works to attain salvation, and the Longleat sermon which focuses on the woman of Canaan and Mary Magdalene.